Numerical Investigation of Large Wood Evolution Characteristics Transported by Flash Floods - SONG Siyuan; FEI Gaogao; WANG Xiekang (工程科学与技术)
ObjectiveDuring floods, wood scattered near river channels is subjected to the action of water flows and transported downstream. In this process, special locations such as bridges, the outer sides of river bends, or channel constrictions are impacted by large wood, which can accumulate and form logjams. The formation of these logjams alters surrounding water flow conditions, leading to the rise of upstream water levels and sedimentation. These scenarios directly affect the stability and safety of bridges and dams. Currently, most numerical models primarily consider the coupling of two-dimensional flow fields with two-dimensional large wood motion models (2D-2D) or three-dimensional flow fields with two-dimensional large wood motion models (3D-2D). However, two-dimensional motion models for large wood cannot represent the vertical structure of logjams, which is equivalent to simulating large wood movement and accumulation only under shallow water conditions or low Froude number conditions. This approach mainly targets rivers with a large width-to-depth ratio in plain areas. However, such rivers typically do not experience large wood blockage issues. Rivers in mountainous areas with a small width-to-depth ratio and significant bends should be the primary consideration for large wood blockage risks. Therefore, most current numerical models have deficiencies, which may lead to underestimating the impacts of large wood blockage disasters. To improve the ability of numerical models to replicate large wood movement and accumulation, a two-way coupling numerical model of three-dimensional flow fields and three-dimensional large wood motion (3D-3D) needs to be adopted.MethodsThe three-dimensional flow field and three-dimensional large wood motion two-way coupling numerical model (3D-3D) presented in this paper is based on the finite volume method and employs a second-order nonlinear k-e model for turbulence calculation. Each piece of large wood is constructed from multiple rigidly connected discrete particles, providing better collision calculation effects and flexibility. The two-way coupling algorithm can reflect the influence of large wood on water flow, thereby allowing the analysis of backwater rise problems caused by logjams. The drag force on large wood is represented by the linear superposition of the forces exerted by the discrete particles constituting the large wood on the water flow. The control equation for large wood considers the combined effects of drag force, water flow acceleration, gravity, virtual mass force, buoyancy, particle collisions, and bed interaction, closely approximating the real conditions governing large wood dynamics.Results and Discussions　The 3D-3D motion and accumulation model was used to simulate the significant large wood transport and accumulation phenomena in the Xihe River of Sanjiang Town during the Wenchuan "8.20" heavy rainfall-induced mountain torrent and debris flow event. Numerical simulation results showed that the transport distance of large wood, under different large wood recruitment, indicated similar distribution behaviors within the river channel. Specifically, large wood distributed in the 100~200 m and 400~500 m sections accounted for 14%~31% and 51%~71% of the total recruitment, respectively. However, results derived from larger large wood recruitment were proven to be more statistically significant. It was confirmed that large wood length was just one of many influencing factors, suggesting that further research needs to alter more variables that might impact large wood transport. When the large wood recruitment exceeded 200 pieces, the influence of large wood length on transport distance was not significant. The submergence state of large wood varied at different time points, and a statistical description was conducted using the time-averaged submergence state. While changes in large wood length had some impact on the number and rate of submerged wood, the correlation was not significant, indicating that submergence behavior might be more influenced by external flow fields. When the length of the large wood exceeded 3.6 m, the submergence rate decreased with the increase in recruitment. In the study segment of Xihe River in Sanjiang Town, there were no bridge piers present. Thus, the study did not include the direct impact of bridge piers on large wood transport and accumulation. It was only found that the accumulation phenomenon of large wood tended to occur at channel constrictions and the outer sides of larger river bends, with a preference for the latter under the current conditions. Logjams at channel constrictions were possibly due to large wood being blocked by obstacles ahead under the impact of water flow, reaching a relatively balanced state. At larger bends, logjams were more likely influenced by centrifugal forces or secondary flows, causing large wood to deposit on the riverbank or be compressed, increasing friction with the riverbank. Upstream, near the logjams, water depth was found to be 2~3 cm deeper than in conditions without logjams. The backwater rise phenomenon could be related to the three-dimensional accumulation pattern and the number of large wood pieces in the logjam, necessitating further exploration. At the upstream channel narrowing, the number of large wood pieces forming logjams from shortest to longest was 47, 50, and 52, respectively. Longer pieces of large wood were more likely to intercept subsequent pieces, expanding the accumulation area.ConclusionsThe 3D-3D model was demonstrated to have a good capability in replicating the movement and accumulation of large wood. Simulations of the large wood distribution, submergence, and accumulation in the Xihe River segment of Sanjiang Town revealed the evolution characteristics of large wood transport during mountain torrents. The transport of large wood was not entirely confined to the vicinity of the water flow interface but exhibited three-dimensional movement characteristics over time. Large wood primarily tended to distribute near channel constrictions and larger bends, forming logjams. These logjams exhibited a three-dimensional structure and caused a certain degree of backwater rise.